Pernikahan Beda Agama dalam Perspektif Huzaemah Tahido Yanggo - Ibnu Paqih Hasan (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The issue of interfaith marriage remains a subject of on going discourse within the context of contemporary Islamic law. In the Indonesian context, this polemic has become increasingly intricate due to its entanglement with considerations of religious law and national positive law. The present study endeavors to examine the thoughts of Prof.Huzaemah Thido Yanggo, a distinguished female scholar dan expert Islamic law, regarding the legal framework of interfaith marriage and her contribution to the discourse of Islamic family law. The present research employs a qualitative methodology, adopting a juridical-normative approach and library research techniques. The primary source is “Masail Fiqhiyah: Kajian Hukum Islam Kontemporer”, complemented by other academic references. The results indicate that Huzaemah categorically prohibits all forms of interfaith marriage, including those between Muslim men and women ahlul kitab. Her perspective is founded on the principle of sad al-dzariah, a concept aimed at averting detrimental consequences (mafsadat), in addition to the maqashid al-syari’ah approach, which emphasizes the preservation of religious integrity, the continuity of offspring, and the maintenance of family stability. Huzaemah’s thought process exhibits a synthesis between normative firmness and sensitivy to the Indoensia social context. This research underscores the signifance of the contibutions of women scholars in contemporary Islamic legal discourse, particularly in matters of critical concern, such as interfaith marriage.